Demand Curves in Theory and in Practice - Gilboy, Elizabeth Waterman (Quarterly Journal of Economics, 1930)
I. The use of theory in the interpretation of statistical demand curves, 601. — II. The equilibrium analysis; its assumptions; the difficulties of applying it to statistical curves, 603. — III. Dynamic curves interpreted with the time element left in, as (a) paths of equilibrium, on the basis of the equilibrium analysis; (b) moving schedules, with different assumptions. Marshall's view, 608. — IV. A possible application of the static analysis; all time elements eliminated from the statistical curves; Moore's curves and their meaning; dynamic curves not demand curves in the orthodox sense; the concept of elasticity not applicable to such curves; present statistical curves neither dynamic nor static; not to be interpreted in terms of orthodox theory, 614.